Neonatal lupus erythematosus. - Coelho, Raquel (2007)
Neonatal lupus erythematosus (NLE) is a rare immune disease. Clinical findings include congenital heart block (CHB), cutaneous manifestations, and hepatic and haematological abnormalities. The authors present a case of a baby with prenatal diagnosis of bradycardia. On the first day of life, she was bradycardic and a CHB (Mobitz type II) with left branch complete block was diagnosed. She had no structural cardiac abnormalities on the scan. Spontaneous resolution of the CHB occurred and she was discharged on the seventh day of life. On the third month of life cutaneous lesions and alimental difficulties were noted. She was diagnosed a complete heart block and a definitive pacemaker was instituted with clinical improvement. Anti-Ro antibodies were positive in the mother and in the child, with the skin biopsy consistent with NLE. Heart block is usually permanent but it can spontaneously revert temporarily to sinus rhythm. A long term follow-up is essential.